2014
DOI: 10.1002/adsc.201400568
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Selective Synthesis of E‐Vinylamines via Tungsten(0)‐Catalyzed Hydroamination of Terminal Alkynes

Abstract: The hydroamination of terminal alkynes (RC CH = phenylacetylene, 4-methylphenylacetylene, 4-fluorophenylacetylene, 1-hexyne, methyl 2propynyl ether, prop-2-yn-1-ol) with secondary amines (piperidine, pyrrolidine, morpholine, piperazine, methylpiperazine, 4-methylpiperidine and 3methylpiperidine) was achieved in high yield (up to 99%), regioselectivity (only anti-Markovnikov product) and stereoselectivity (only E-isomers) within a maximum of 5 h in reactions catalyzed by the tungsten tetracarbonyl complex cis-[… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…It has been suggested that dirhodium vinylidene 334 , an isolable intermediate, is a catalyst resting state and exists in equilibrium with the mononuclear vinylidene complex 333 that enters into the catalytic cycle . Another intermolecular hydroamination reaction employing a W­(CO) 4 (piperidine) 2 catalyst has been reported producing enamine products with good yield …”
Section: Catalytic Reactions Of Metal-complexed Alkenylidenes: Carbon...mentioning
confidence: 99%
“…It has been suggested that dirhodium vinylidene 334 , an isolable intermediate, is a catalyst resting state and exists in equilibrium with the mononuclear vinylidene complex 333 that enters into the catalytic cycle . Another intermolecular hydroamination reaction employing a W­(CO) 4 (piperidine) 2 catalyst has been reported producing enamine products with good yield …”
Section: Catalytic Reactions Of Metal-complexed Alkenylidenes: Carbon...mentioning
confidence: 99%
“…Significant progress has been made in catalyzed hydroamidation, and high levels of chemo-, regio-, and stereo-selectivity have been reported 4 , 11 – 13 . However, currently reported examples are mainly centered on hydroamidation 14 17 of terminal alkynes 9 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…In this context, hydroamination of alkynes has been studied extensively to prepare nitrogen-containing molecules with high atom efficiency, but there are still limitations in the functional group tolerance and the substrate scope. For example, few reports have been made on anti-Markovnikov addition of secondary amines to alkylacetylenes, which are relatively less electrophilic than arylacetylenes. …”
mentioning
confidence: 99%